Associações de cultivares de caupi-hortaliça com cultivares de rabanete adubadas com flor-de-seda - Azevedo, Iara Beatriz Silva (Universidade Federal Rural do Semi-Árido, 2018)
The objective of this work was to evaluate an agroeconomic performance of associations of cowpea-vegetable cultivars with radish cultivars fertilized with Calotropis procera. The experiment was conducted at the Rafael Fernandes Experimental Farm of the Universidade Federal Rural do Semi-Árido (UFERSA) from May to December 2017. The experimental design was a randomized complete block design with treatments arranged in a 4 x 2 factorial scheme, with 4 replicates from the combination of four cultivars cowpea-vegetable (BRS Tumucumaque, BRS Cauamé, BRS Guariba and BRS Itaim) with two cultivars radish (Crimson Gigante and Zapp). In each block, single plots of the studied cultivars were planted to obtain the agronomic indices. In the radish crop, evaluations were performed at plant height, in fresh and dry mass of shoots, in the productivities total, commercial and noncommercial of roots. In the cowpea-vegetable were evaluated green pod, length, number of green pods per square meter, productivity and dry mass of green pods, number of green grains per pod, productivity and dry mass of green grains. The agro-economic indices evaluated in the intercropped systems were land equivalent ratio, productive efficiency index, score of the canonical variable (Z), system productivity index, actual yield loss, aggressivity, competitive ratio, gross income, net income, rate of return, and profit margin. Univariate analyses of variance for the randomized block design were performed on the characteristics of each crop in the intercropping, as well as on the determined agro-economic indices. A multivariate analyses of variance was also performed on the yields of the intercropped vegetable crops to obtain the canonical variable score (Z), as function of treatment factors. The mean data were compared by the Tukey test at the 5% probability level. The association of cultivars with greater agro-economic efficiency was composed of the cultivar BRS Tumucumaque with the cultivar Crimson Gigante. The radish was the dominant culture and the cowpea-vegetable was the dominated culture. The radish intercropping with cowpea-vegetable is feasible with Calotropis procera
Associations of cowpea cultivars with cultivars of radish cultivated with silk flower
Keywords: Desempenho agro-bioeconômico; Vigna unguiculata; Raphanus sativus; Agrobioeconomic performance; Vigna unguiculata; Raphanus sativus; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA